Rocket to limbo - Nourse, Alan E. (Alan Edward), 1928- (Faber and Faber, 1964)
An ecologist finds himself aboard a star ship where some of the crew mutiny when they discover they are not on a routine run, but a landing is made on an unknown planet and they encounter an alien race with extrasensory powers.